Adaptive Neuro-Fuzzy-based Vibration Approach for Structural Fault Diagnosis - Hakim, S. J. S.; Kamarudin, A. F.; Mokhatar, S. N.; Jaini, Z. M.; Umar, Sarehati; Mohamad, Noridah; Jamaluddin, Norwati (International Journal of Integrated Engineering, 2022)
In recent times, damage identification based on vibration methods are emerging as common approaches, in which the techniques apply the vibration response of a monitored structure, such as modal frequencies and damping ratios, to evaluate its condition and detect structural damage. The basis of the vibration-based health monitoring method is that when there are alterations in the physical characteristics of a structure, there will also be changes in its vibration properties. This paper proposed a neuro-fuzzy artificial intelligence method, called adaptive neuro-fuzzy inference system (ANFIS), to detect damage using modal properties. To generate the modal characteristics of the structures, experimental study and finite element analysis of I-beams with single damage cases were performed. The results showed that the ANFIS approach was able to detect the magnitude and location of the damage with a significant degree of precision, and notably reduced computational time.